2015
DOI: 10.3762/bjnano.6.105
|View full text |Cite
|
Sign up to set email alerts
|

From lithium to sodium: cell chemistry of room temperature sodium–air and sodium–sulfur batteries

Abstract: SummaryResearch devoted to room temperature lithium–sulfur (Li/S8) and lithium–oxygen (Li/O2) batteries has significantly increased over the past ten years. The race to develop such cell systems is mainly motivated by the very high theoretical energy density and the abundance of sulfur and oxygen. The cell chemistry, however, is complex, and progress toward practical device development remains hampered by some fundamental key issues, which are currently being tackled by numerous approaches. Quite surprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
381
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 402 publications
(401 citation statements)
references
References 258 publications
4
381
0
5
Order By: Relevance
“…Ein umfassender Vergleich zu diesem Thema findet sich an anderer Stelle. [12] Wieo ben erwähnt, werden regelmäßig Übersichtsartikel Grundsätzlich lassen sich also auch mit Natriumionenbatterien hohe Spannungen erzielen. Betrachtet man Lithium und Natrium im Vergleich, so sollte Natrium aufgrund der geringeren Kohäsionsenergie Zellspannungen ermçglichen, die sogar um 0.53 Vh çher liegen.…”
Section: Einführungunclassified
“…Ein umfassender Vergleich zu diesem Thema findet sich an anderer Stelle. [12] Wieo ben erwähnt, werden regelmäßig Übersichtsartikel Grundsätzlich lassen sich also auch mit Natriumionenbatterien hohe Spannungen erzielen. Betrachtet man Lithium und Natrium im Vergleich, so sollte Natrium aufgrund der geringeren Kohäsionsenergie Zellspannungen ermçglichen, die sogar um 0.53 Vh çher liegen.…”
Section: Einführungunclassified
“…[1][2][3][4][5][6][7][8][9][10] The composition of discharge products can be regulated by tuning their reaction conditions such as adding redox mediators [11][12][13][14][15][16][17][18] and changing electrochemical environment. [19][20][21][22][23] Some monovalent discharge products such as LiOH 18 and LiO 2 23 could be formed by adding some mediators and controlling electrode structures.…”
Section: Introductionmentioning
confidence: 99%
“…3,9,24,25 However, there exist a large debates on discharge product such as NaO 2 , Na 2 O 2 , and Na x O 2 (1<x<2) in Na-O 2 batteries duo to very close equilibrium voltages. 9,20,25,26 Based on ex situ analysis of the carbon cathode, Fu et al reported Na 2 O 2 as the major discharge product with use of either carbonate or ether electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relatively poor performance of the existing battery concepts represents the major bottleneck for the further developments of "mobile energy". The currently most common technologies are based on lithium compounds (also a substitution with sodium is intensively discussed) [6]. However, the application of LiCoO 2 as the cathode-active material leads to problems in terms of thermal stability as well as cost, toxicity, and availability of the raw-materials [1].…”
mentioning
confidence: 99%